Comparing the Teachings of Fasting in Christianity and Islam: A Reflective Comparison - Alfian, Andi (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Fasting is one of the religious practices or rituals/worship found in almost every religious tradition, including the Christian and Islamic religious traditions. Several scholars of religious studies, through various research, claim that fasting was practiced thousands of years ago by various religious adherents in the world and persists to this day. This study attempts to describe the teachings and practices of fasting in Christianity and Islam and then provides an analysis of the similarities and differences in implementing these teachings in the context of Indonesia. This study is library research in the sense that this study will rely on books and scientific journals related to this topic as primary data sources. This study found that the practice of fasting in Christianity and Islam each has its meaning, uniqueness, and characteristics. For example, they have their meaning about the purpose of fasting, the arguments they use for fasting, the types of fasting, and the procedures. Furthermore, this study argues that religious teachings, both Christianity and Islam, are dynamic, multi-interpretative, and contextual.